2022
DOI: 10.1002/smll.202206628
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Graphitization Behavior in Near‐Surface/Interface Region of Polymer‐Derived Ceramics

Abstract: A free carbon phase has been proven to be beneficial for many structural and functional properties of PDCs, such as electrical conductivity, [8][9][10][11][12][13][14] electromagnetic properties, [15][16][17] electrochemical properties, [18,19] piezoelectricity, [20,21] corrosion resistance, [22] and oxidation resistance. [23] In high-temperature sensing applications, the concentration and morphology of free carbon strongly affect the electrical properties of devices and the selectivity/sensitivity of sensors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 87 publications
1
5
0
Order By: Relevance
“…Interestingly, the graphene shell is formed only in those regions of the SiAlCO PDCs that were exposed to the e-beam, indicating the need for high energy input. Similar graphenization of the near-surface/interface region and the formation of graphene-like layers was also observed in silicon based PDCs obtained from different deposition techniques, such as direct ink writing (DIW) additive manufacturing or spark plasma sintering of powders. , However, the literature reported formation of graphene-like layers in silicon-based PDCs only at pyrolysis temperatures above 1200 °C, while in this work, the layers grew at considerably lower temperatures, starting at 800 °C, which confirms that the e-beam plays a role in the transformation. It is likely that the e-beam provides an additional energy increment needed for the conversion of the decomposed organic groups to graphene.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Interestingly, the graphene shell is formed only in those regions of the SiAlCO PDCs that were exposed to the e-beam, indicating the need for high energy input. Similar graphenization of the near-surface/interface region and the formation of graphene-like layers was also observed in silicon based PDCs obtained from different deposition techniques, such as direct ink writing (DIW) additive manufacturing or spark plasma sintering of powders. , However, the literature reported formation of graphene-like layers in silicon-based PDCs only at pyrolysis temperatures above 1200 °C, while in this work, the layers grew at considerably lower temperatures, starting at 800 °C, which confirms that the e-beam plays a role in the transformation. It is likely that the e-beam provides an additional energy increment needed for the conversion of the decomposed organic groups to graphene.…”
Section: Resultssupporting
confidence: 82%
“…This is in good agreement with the TEM investigations that did not show graphene in the PDC bulk. In addition to that, the Raman signals of the locations (7,9,13,17,19) of SiAlCO PDCs showed fluorescence, suppressing the second-order wavenumber range of the Raman spectrum, which is correlated with the presence of sp 2 -carbon clusters in the amorphous matrix of the film.…”
Section: ■ Results and Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The strain sensing properties of C/SiCN thin-film strain gauge were tested by deflection method. [71] Its gauge factor (GF) was determined as 23. The stable signal output of 5000 fatigue tests of the C/SiCN thin-film strain gauge indicated that the insulation layer had good fatigue tolerance.…”
Section: Application Of Vein-membrane Al 2 Omentioning
confidence: 99%